The role and effect of companions during childbirth in Oman - Nasar Alwahaibi; Rodina AL-Julandani; Alzarah Al-Kalbani (BMC, 2024)
Abstract Background There is increasing evidence that a companionship is an important tool for improving the quality of care provided to pregnant women during the labour and delivery process. The literature review shows very limited studies assessing the role of companions during childbirth from the companion's point of view. Many published papers studied the role and satisfaction of pregnant women but not their companions. Therefore, this study aimed to assess the role and effect of companions during childbirth in Oman. Methods This cross-sectional observational study was conducted at Sultan Qaboos University Hospital, Oman, between June 2022 and April 2023. Companions were interviewed face-to-face at a time convenient to them. A telephone interview was conducted with those who left the hospital early. The questionnaire comprised sociodemographic data and other sections, including the nature of the help provided by the supportive companion, their effects on the women who gave birth, and the timing of their presence during companionship. Results A total of 214 companions were included in this study with the mean age of 42.54 years. The most common relationship to the pregnant women was mothers (35.7%), followed by husbands (30.5%). The majority of companions provided support during admission (62.6%), in the immediate post-partum ward (56.5%) and during delivery (54.2%), while a minority helped from admission to discharge (22.4%). The most common type of support provided was encouraging words (89.7%) followed by transferring things (43.9%), massage (37.4%) and touch (33.6%). The majority of companions (96.7%) reported that their support helped very much, and the pregnant women felt better and calmer. Conclusions Labouring women felt better and calmer because of the presence of companions. Companions preferred to be present in the postpartum and during labour and delivery. The majority of companions support their labouring women by encouraging wards. Companions love and encourage others to support their labouring women during their critical times.